Upregulating Nonneuronal Cholinergic Activity Decreases TNF Release from Lipopolysaccharide-Stimulated RAW264.7 Cells - Yi Lv; Sen Hu; Jiangyang Lu; Ning Dong; Qian Liu; Minghua Du; Huiping Zhang (Mediators of Inflammation)
Nonneuronal cholinergic system plays a primary role in maintaining homeostasis. It has been proved that endogenous neuronal acetylcholine (ACh) could play an anti-inflammatory role, and exogenous cholinergic agonists could weaken macrophages inflammatory response to lipopolysaccharide (LPS) stimulation through activation of α7 subunit-containing nicotinic acetylcholine receptor (α7nAChR). We assumed that nonneuronal cholinergic system existing in macrophages could modulate inflammation through autocrine ACh and expressed α7nAChR on the cells. Therefore, we explored whether LPS continuous stimulation could upregulate the nonneuronal cholinergic activity in macrophages and whether increasing autocrine ACh could decrease TNF release from the macrophages. The results showed that, in RAW264.7 cells incubated with LPS for 20 hours, the secretion of ACh was significantly decreased at 4 h and then gradually increased, accompanied with the enhancement of α7nAChR expression level. The release of TNF was greatly increased from RAW264.7 cells at 4 h and 8 h exposure to LPS; however, it was suppressed at 20 h. Upregulating choline acetyltransferase (ChAT) expression through ChAT gene transfection could enhance ACh secretion and reduce TNF release from the infected RAW264. 7cells. The results indicated that LPS stimulation could modulate the activity of nonneuronal cholinergic system of RAW264.7 cells. Enhancing autocrine ACh production could attenuate TNF release from RAW264.7 cells.